The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/9621615
|View full text |Cite
|
Sign up to set email alerts
|

Direct Bilirubin Levels and Risk of Metabolic Syndrome in Healthy Chinese Men

Abstract: Background Serum bilirubin is a potent endogenous antioxidant with anti-inflammatory properties. Several cross-sectional studies have reported that bilirubin was negatively associated with metabolic syndrome. However, in recent longitudinal studies, the relations between bilirubin and metabolic syndrome are inconsistent. Moreover, previous studies mainly focused on serum total bilirubin which is the sum of direct bilirubin and indirect bilirubin. For these reasons, the longitudinal effect of bilirubin subtypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 39 publications
1
22
2
1
Order By: Relevance
“…First, we did not quantify individual food consumption prior to or during the 24 h experimental period, which could have important explanatory power regarding body mass. Second, our predictions were derived from work with humans exhibiting metabolic syndrome, which is characterized by factors such as obesity, inflammation and hypertension (Li et al, 2017;Vanella et al, 2014). These human individuals exhibit both lower levels of bilirubin (the reduced form of biliverdin; Li et al, 2017) and lower activity of HO (Vanella et al, 2014), which is why we predicted that lower levels of biliverdin might be associated with higher levels of triglyceride-associated metrics.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, we did not quantify individual food consumption prior to or during the 24 h experimental period, which could have important explanatory power regarding body mass. Second, our predictions were derived from work with humans exhibiting metabolic syndrome, which is characterized by factors such as obesity, inflammation and hypertension (Li et al, 2017;Vanella et al, 2014). These human individuals exhibit both lower levels of bilirubin (the reduced form of biliverdin; Li et al, 2017) and lower activity of HO (Vanella et al, 2014), which is why we predicted that lower levels of biliverdin might be associated with higher levels of triglyceride-associated metrics.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our predictions were derived from work with humans exhibiting metabolic syndrome, which is characterized by factors such as obesity, inflammation and hypertension (Li et al, 2017;Vanella et al, 2014). These human individuals exhibit both lower levels of bilirubin (the reduced form of biliverdin; Li et al, 2017) and lower activity of HO (Vanella et al, 2014), which is why we predicted that lower levels of biliverdin might be associated with higher levels of triglyceride-associated metrics. However, metabolic syndrome is also associated with overweight individuals circulating higher levels of triglycerides (Wu et al, 2011), and because we found that the largest birds did not have significantly higher levels of circulating triglycerides, humans exhibiting metabolic syndrome may not be an appropriate group from which to generate predictions between body mass and circulating biliverdin levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations